First observations of quasi 120 day oscillation in Mesospheric winds and temperature: Observations inferred from Meteor Radar. Issue 3 (19th June 2013) - Das, Siddarth Shankar; Kishore Kumar, Karanam; Ramkumar, Geetha
Abstract [1] For the first time, the presence of quasi 120 day oscillation in the neutral winds and temperature at mesosphere and lower thermosphere (MLT) region, measured using meteor wind radar over an equatorial station Thumba (8.5°N, 76.5°E) is discussed. The amplitudes of quasi 120 day oscillation as a function of height have been established over Thumba. The origin of the quasi 120 day oscillation in geophysical parameters at MLT heights are discussed in terms of the atmospheric angular momentum, F10.7, and Lyman‐alpha solar flux and nonlinear interactions between annual and semiannual oscillations. The significance of the present study lies in providing the observational evidence for quasi 120 day oscillation in the MLT region and in discussing the possible source mechanisms for the observed oscillation.